(untitled) (The International Journal for Scientific Research, 2024)
This study aims to determine the impact of training on the performance of employees in private sector institutions in the city of Riyadh. The study focuses on a deep understanding of the impact that training can achieve in improving employees’ performance and developing their skills in the work environment. Training is viewed as a strategic tool to enhance efficiency and effectiveness in organizations. The study is based on a comprehensive research methodology that includes collecting data from several institutions in the private sector in the city of Riyadh. Appropriate research tools, such as questionnaires, are used to collect data relevant to training and employee performance. Through this study, it is expected to be of great importance to decision-makers and managers in private sector organizations, as it will provide valuable insights into the effectiveness of training and its impact on employee performance. Based on the results of the study, training strategies can be improved and performance and efficiency enhanced in organizations.